Biotechnology from A to Z - Bains, William (Oxford University Press, 2004)
In 300 entries that span from ADEPT through cloning, genomes, patents, and viruses to zoonosis, Biotechnology from A to Z provides the essential guide to newly coined terms, and is an invaluable resource for anyone wanting access to the world of Biotechnologists. Recommended reading for scientists and non-scientists alike, it can be read cover to cover, or dipped into for a quick understanding of a term or topic.